Теорії міфу та ритуал центру в українській міфологічній картині світу: традиційність та новаційність ритуалу - Віктор, Ірина Володимирівна (Харківський національний університет ім. В. Н. Каразіна, 2013)
Досліджено витоки українських традицій, пов'язаних з структуруванням простору та часу, зв'язок міфів та ритуалів центру в українській міфологічній картині світу. Доводиться, що міф центру сприяє оновленню традиції, форми реалізації традиції різноманітні, але основними з них є звичай, свято та обряд. Міфологія центру в сучасних та традиційних суспільствах змінюється, але залишаються її основні компоненти – виділення сакрального простору, центрування та об'єднання всієї общини навколо спільних цінностей, виділення особливої структури у часі і просторі, накладання символіки сакрального центру тієї чи іншої культури на інші культурні реалії цієї національної культури, що стає своєрідним основним символом цієї культури, відкриває зв'язок з метафізичними та трансцендентними началами. Міфологія центру в українській традиційній міфологічній картині світу співвідносна з храмом, пізніше місцем християнської літургії, та місцем зібрання громади, общини, пізніше місцем проведення свята.

Investigated the origins of Ukrainian traditions associated with the structuring of space and time, the relationship of myth and ritual of center in the Ukrainian mythological worldview. It is proved that the myth center promotes updating traditions, modalities traditions vary, but the chief among them are custom, celebrations and ceremonies. In this study, concepts of tradition and ritual were used as similar, of the same order, with the ritual we have seen both traditional and innovation-elements (e.g., rituals and Post-Soviet era, the rituals of the modern nation-state and corporate rituals). Tradition is based on ritual. Regarding ritual, there are three main groups of theories. The first group of theories linked to the myth of ritual is mythopoetic theory of ritual, where ritual is an illustration of the myth, and the myth is a kind of script. The best known of this group of theories are Potebnya, Losev, M.Eliade, Toporov. The second group of theories is in the context of considering the ritual sacrifices and sacrifice where the main acts of the community deliverance from sin, guilt, through certain rituals, so this theory cleansing ritual, where ritual facilitates release of the community from the mistakes and crimes of the past. The third group of theories of ritual has biologizing character which connects the rituals of animals and men, speaking of cultural specificity of the ritual, it is removed from the origin of the instinctive behavior of animals. The most well-known supporter of this theory is especially important Konrad Lorenz theory. Thе mythopoetic ritual that binds to certain symbolic unity of myth and ritual - the ritual illustrates the myth. This close interaction, the connection of myth and ritual tradition is the basis of power, and its actualization. Tradition builds a mythological world view, which characterizes a particular national culture. At the foundation of this tradition there is a definite set of myths and a few basic rituals, which are the most important of the mythological world picture ritual center. Mythology center of modern and traditional societies change, but retains its main components - a selection of sacred space, alignment and unification of the entire community around shared values, the allocation of a special structure in time and space, the imposition of the symbolism of the sacred center of a culture to other cultural realities of this national culture. Thus it becomes a kind of sacred center of the main character of this culture, opens the connection to the metaphysical and transcendental principles. Mythology center in Ukrainian traditional mythological picture of the world is related to the church, later a place of Christian liturgy, and the meeting place of the community, and later the venue for the festival. When profanic tradition is established, creating stereotypes of colonial church replaced tavern and one metaphysical element of the community association is a song. In Ukrainian culture mythology associated with the center screen ("screen", "TV" culture), and location / time of celebration. A song can store the value of the metaphysical center of the Ukrainian community, and perhaps parody, technology of mass media and mass culture. Ukrainian mythological world picture retains its main characters, is the development and updating of the national mythology about the basic mythological landmarks, including the myth of the center.
Theory of myth and ritual center of ukrainian mythological picture of the world: traditional and innovative ritual
Keywords: міф; ритуал; традиція; новація; сакральний простір; національний міф; символ; myth; ritual; tradition; innovation; sacred space; national myth; symbol